(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
In Uzbekistan, extensive measures are being taken to develop resource-saving equipment and devices with low energy and metal consumption and high efficiency for livestock farms. Decree No. PF-60 of the President of the Republic of Uzbekistan of January 28, 2022 "On the development strategy of New Uzbekistan for 2022-2026" and PQ-4576 of January 29, 2020 "On additional measures of state support for the livestock industry" the tasks specified in numerous decisions and other normative-legal documents related to this activity are being implemented [1].